Delayed versus emergency hepatectomy for ruptured hepatocellular carcinoma - Chotirosniramit Anon (2018)
Background and Aims: Ruptured hepatocellular carcinoma (HCC) is a life-threatening complication of HCC. Delayed hepatectomy after successful hemostasis or emergency hepatectomy is the controversial issue of the treatment for resectable ruptured HCC. The aim of this study was to evaluate outcomes of these procedures for ruptured HCC. Materials and Methods: From 2001 to 2005, hepatectomy for HCC was performed by the author on 62 patients, Of these, 16 patients had ruptured HCC. Emergency hepatectomy was performed in 10 patients and delayed hepatectomy in the remaining 6. Clinical data and outcomes following hepatectomy for ruptured HCC were reviewed and analyzed retrospectively. Results: In emergency hepatectomy group, there was one complication of transient gastric atony and one of postoperative death from massive variceal bleeding. A 1 -year survival rate was 60% with a mean survival of 22 months. No postoperative complication and death was found in delayed hepatectomy patients but three died in 8, 11 and 14 months due to lung metastasis. A 1 -year survival rate was 67% with a mean survival of 14 months. No statistically significant difference in morbidity and mortality rate was found between the emergency hepatectomy group and delayed or elective hepatectomy group. There was no significant difference in overall survival between emergency and delayed hepatectomy groups. Conclusion: Emergency hepatectomy may be a life-saving procedure for resectable ruptured HCC patients who have massive and continuous bleeding, particularly if emergency transarterial embolization is not available. To avoid difficult delayed hepatectomy and with concern for the rapid progression of cancer, delayed hepatectomy should be performed as soon as possible.